Haptic glove for tactile graphics reader - Shamsul Bahrin, Muhammad Ikmal Hakim; Norasram, Muhammad Izzaiman; Md Yusof, Hazlina; Ghazali, Aimi Shazwani; Sidek, Shahrul Na'im (UTeM Press, 2023)
Tactile graphics are commonly used reading materials by blind and visually impaired (BVI) students to access graphical information in STEM subjects. However, reading graphical information using haptic senses is far more difficult compared to reading visual-based information. It is a cognitive overload task due to the complexity of graphical information represented in a tactile format. Without any guidance or assistance from a sighted person, the BVI reader could not read and comprehend the information on the tactile graphics independently. This current study aims to design an assistive device that uses a haptic feedback method to provide artificial directional cues provided by four vibrating mini motor discs. An exploratory test with 10 blindfolded (BF) participants has been conducted to investigate several design factors and configurations of the haptic glove of the assistive device. The results showed that the most effective configuration for the current design is when the four mini motor discs are placed at the hand palm and are set to high-intensity vibration for the cues.